Deep Learning Model Integrated with Intercultural Pragmatic Competences in Improving EFL Learners’ Speaking Skills - Haerazi Haerazi; Lalu Ari Irawan (Jurnal Ilmiah Global Education, 2026)
This study investigated the integration of a deep learning model with intercultural pragmatic competence to improve EFL learners’ speaking skills. The study was motivated by the need to develop speaking instruction that goes beyond grammatical accuracy and fluency by incorporating meaningful communication, learner reflection, pragmatic appropriateness, and intercultural awareness. A qualitative research design was employed to explore teachers’ experiences and classroom practices in applying deep learning-oriented speaking activities. The participants were seven EFL teachers who had experience implementing a deep learning model in their English classes. Data were collected through semi-structured interviews and classroom observations. The data were analyzed through data condensation, data display, and conclusion drawing. The findings revealed that the deep learning model contributed to learners’ speaking development by encouraging meaningful speaking practice, collaboration, problem-solving communication, learner autonomy, and self-reflection. Activities such as role-plays, group discussions, simulations, dialogue analysis, and problem-based tasks helped learners express ideas, negotiate meaning, and build confidence in using English. The findings also showed that integrating intercultural pragmatic competence enabled learners to speak more appropriately and effectively in intercultural contexts. Learners were guided to understand politeness strategies, speech acts, indirect expressions, turn-taking, social distance, and cultural norms in communication. This integration helped learners become more aware of how language choices should be adjusted according to context, relationship, and communicative purpose. The study concludes that combining deep learning principles with intercultural pragmatic competence provides a meaningful pedagogical framework for developing EFL learners as fluent, reflective, culturally responsive, and pragmatically competent speakers.